Nonlinear stability analysis of whirl flutter in a tiltrotor rotor-nacelle system - Mair, C.; Rezgul, D.; Titurus, B. (My University, 2017)
Whirl flutter is an aeroelastic instability that affects propellers/rotors and the vicinity in which they are mounted. Whirl flutter analysis in tiltrotors gets progressively more complicated with the addition of nonlinear effects. This paper investigates the impact of nonlinear pylon stiffness on the whirl flutter stability of a basic rotor-nacelle model, compared to a baseline linear stiffness version. The nonlinearity investigated in this paper is cubic stiffening of both softening and hardening profiles. The investigation is conducted through a combination of simulations, eigenvalue and bifurcation analyses, in order to fully capture the effects of spring nonlinearity on the dynamic behaviour of the rotor-nacelle system. The analysis provides a more complete stability envelope, demonstrating the complex behaviour of the rotor-nacelle system in the presence of cubic stiffening. The results illustrate the coexistence of stable and unstable limit cycles and equilibria for a range of parameter values. The results also demonstrate the importance of nonlinear whirl flutter models and analysis methods. Of particular interest are cases where the dynamics of the nacelle are unstable despite linear analysis predicting stable behaviour.